Peningkatan Proses dan Hasil Belajar Matematika Menggunakan Modelkooperatif Tipe Take and Give di Kelas IV SDN 138/II Daya Murni - Sisca Puspitasari; Randi Eka Putra; Aldino Aldino (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to address the low learning process and outcomes of students in mathematics in grade IV of State Elementary School 138/II Daya Murni. The type of research used is classroom action research (CAR), which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects in this study were 13 students, and the implementation was carried out in the second semester of the 2025 academic year. Data were collected through observation, field notes, documentation, and learning outcome tests. Based on the results of the study, the Take and Give Type Cooperative model was proven to be able to improve the learning process and outcomes of students. In the first cycle, the involvement of educators in teaching was recorded at 66.66%, while in the second cycle it increased to 73.33%. Likewise, student involvement in the learning process increased from 46.61% in the first cycle to 69.23% in the second cycle. A significant increase was also seen in the completeness of student learning outcomes. In cycle I, the learning achievement rate reached 76.92%, and in cycle II, it increased to 84.61%. The implementation of the Take and Give Cooperative Model has proven effective in improving the quality of learning, both in terms of process and outcomes. Therefore, this model can be a useful alternative for educators in increasing student engagement and learning outcomes in grade IV.